P, t-[Ru(CO)(PR3)(tren)]2+ [R = Ph or p-tol; tren = tris(2-aminoethyl)amine], Ru(II) complexes bearing a simple tripodal tetradentate amine: synthesis, characterization, and antimicrobial activity. Issue 18 (16th September 2016) - Fagundes, Francisco D.; Reis, John D.; Appelt, Patricia; Cavarzan, Deividi A.; Murakami, Fábio S.; Scopelliti, Rosario; Dyson, Paul J.; De Araujo, Márcio P.
Abstract: Complexes with general formula p, t -[Ru(CO)(PR3 )(tren)]X2 [R = Ph (1 ) or p -tol (2 ); tren = tris(2-aminoethyl)amine; X = Cl − or ] were prepared from [RuCl2 (CO)(dmf)(PR3 )] by direct reaction with tren. The complexes were fully characterized by NMR ( 1 H, 31 P{ 1 H}, HMBC 1 H– 31 P), FTIR and ESI-MS spectroscopy, elemental analysis, and the structures of p, t -[Ru(CO)(PPh3 )(tren)](PF6 )2 (1PF 6 ) and p, t -[Ru(CO)(P{ p -tol}3 )(tren)]Cl2 (2Cl ) were determined by X-ray diffraction. The water soluble complexes1Cl and2Cl were tested as antimicrobial agents against Gram (+) and Gram (−) bacteria with the latter showing superior activity than the approved antimicrobial agent chloramphenicol in one of the strains. Abstract :